Answer:
-21
Step-by-step explanation:
-6x + 2y = -18.........(i)
-3x - 2y = 54...........(ii)
add equ.(ii) to equ. (i)
(-6x + [-3x]) + (2y + [-2y]) = -18 + 54
-9x = 36
x = -4
sub x= -4 into equ (i)
-6(-4) +2y = -18
24 + 2y = -18
24 +18 = -2y
42 = -2y
y = -21
Most of the time it will be Length x Width x Height.
Answer:
What is the surface
Step-by-step explanation:
U should put a pic or something so we can help u <3 btw can u give me a brainllest cuz i need 1 more to hit 5 thank u <3
The image that shows the reflection of DFEG over the x-axis is the FIRST option. The x-axis is the mirror line. The distance from the mirror line to the reflected shape equals to the distance from the original image to the mirror line.